PENGENALAN TERIPANG DAN MANFAATNYA DI PERAIRAN HUTUMURI BAGI SISWA SMP NEGERI 8 AMBON - Lewerissa, Yona A; Uneputty, Prulley A (Pattimura University, 2023)
Hutumuri waters have sea cucumber resources, but their utilization is still limited. However, there are exploitation activities of their habitat. Therefore, the community service activity was carried out, which aimed to provide knowledge and increase the role of SMP Negeri 8 Ambon students in conserving sea cucumber resources. The activity was conducted online by using various lecture methods, video playback, discussion and sharing of experiences by students, and provision of ebooks. The results of the evaluation by the pre-test and post-test indicated that the knowledge of students increased about the important of sea cucumber. It is expected that this activity will motivate students to be sustainable agent who play an important role to maintain the sustainability of sea cucumber resources and both coastal and marine ecosystems.